Compensation for industrial pollution damage in Algerian legislation - Boulakouas, Yousra; Boulakouas, Sara; Henni, Abdesselam; Benazzoug, Mounir (The International tax journal, 2025)
Industrial pollution causes damage to elements of the natural environment (air, water, soil), which then reflects on humans, causing various physical, material, and moral harms. These damages are remedied through the establishment of civil liability, which concludes with either specific compensation or monetary compensation. Given the particular nature of these damages, there are challenges in compensating for them, especially the damages affecting the natural environment.